Revision of the Barsine cardinalis–anomala ’species-complex’ (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2017)
The Barsine cardinalis–anomala ’species-complex’ is revised. Five new species (B. pseudocardinalis Volynkin & Černý, sp. nov. from Indochina, B. fansipana Volynkin & Černý, sp. nov. from North Vietnam, B. nangkwak Volynkin & Černý, sp. nov. from North Thailand, B. incompletostriga Volynkin & Černý, sp. nov. from North-East India and B. rawanga Volynkin & Černý, sp. nov. from North Burma) and one new subspecies (B. cardinalis gemina Volynkin & Černý, ssp. nov. from North Thailand) are described. A new combination (Barsine anomala (Elwes, 1890), comb. nov. ), new synonymy (Barsine cardinalis cardinalis (Hampson, 1900) = Miltochrista erubescens Rothschild, 1936, syn. nov.), and six new species-groups are established. Adults, male and female genitalia of all species are illustrated.